Subpopulation targeting of pyruvate dehydrogenase and GLUT1 decouples metabolic heterogeneity during collective cancer cell invasion - Commander, R. (Nat Commun, 2020)
Phenotypic heterogeneity exists within collectively invading packs of tumor cells, suggesting that cellular subtypes cooperate to drive invasion and metastasis. Here, we take a chemical biology approach to probe cell:cell cooperation within the collective invasion pack. These data reveal metabolic heterogeneity within invasive chains, in which leader cells preferentially utilize mitochondrial respiration and trailing follower cells rely on elevated glucose uptake. We define a pyruvate dehydrogenase (PDH) dependency in leader cells that can be therapeutically exploited with the mitochondria-targeting compound alexidine dihydrochloride. In contrast, follower cells highly express glucose transporter 1 (GLUT1), which sustains an elevated level of glucose uptake required to maintain proliferation. Co-targeting of both leader and follower cells with PDH and GLUT1 inhibitors, respectively, inhibits cell growth and collective invasion. Taken together, our work reveals metabolic heterogeneity within the lung cancer collective invasion pack and provides rationale for co-targeting PDH and GLUT1 to inhibit collective invasion.